Pneumocystis pneumonia occurrence and prophylaxis duration in kidney transplant recipients according to perioperative treatment with rituximab - Kim, Young Hoon (BMC Nephrol, 2020)
BACKGROUND: Pneumocystis pneumonia (PCP) is a life-threatening fungal infection that can occur in kidney transplantation (KT) recipients. A growing number of KT recipients are receiving perioperative treatment with rituximab, which is associated with prolonged B-cell depletion and possible risk of PCP occurrence; however, the optimal prophylaxis duration according to rituximab treatment is yet unknown. We compared the occurrence of PCP and the duration of prophylaxis in KT recipients according to rituximab treatment. METHODS: We retrospectively analyzed 2110 patients who underwent KT between January 2009 and December 2016, who were divided into non-Rituximab group (n = 1588, 75.3%) and rituximab group (n = 522, 24.7%). RESULTS: In the rituximab group, the estimated number needed to treat (NNT) for prophylaxis prolongation from 6 to 12 months was 29.0 with a relative risk reduction of 90.0%. In the non-rituximab group, the estimated NNT value was 133.3 and the relative risk reduction was 66.4%. Rituximab treatment (hazard ratio (HR) = 3.09; P <  0.01) and acute rejection (HR = 2.19; P = 0.03) were significant risk factors for PCP in multivariate analysis. CONCLUSIONS: Our results suggest that maintaining PCP prophylaxis for 12 months may be beneficial in KT recipients treated with rituximab for desensitization or acute rejection treatment.